Implementation of pharmacogenetic testing in oncology: DPYD-guided dosing to prevent fluoropyrimidine toxicity in British Columbia - Wu, Angela; Anderson, Helen; Hughesman, Curtis; Young, Sean; Lohrisch, Caroline; Ross, Colin J. D.; Carleton, Bruce C. (Frontiers in Pharmacology, 2023)
Background: Fluoropyrimidine toxicity is often due to variations in the gene (DPYD) encoding dihydropyrimidine dehydrogenase (DPD). DPYD genotyping can be used to adjust doses to reduce the likelihood of fluoropyrimidine toxicity while maintaining therapeutically effective drug levels.Methods: A multiplex QPCR assay was locally developed to allow genotyping for six DPYD variants. The test was offered prospectively for all patients starting on fluoropyrimidines at the BC Cancer Centre in Vancouver and then across B.C., Canada as well as retrospectively for patients suspected to have had an adverse reaction to therapy. Dose adjustments were made for variant carriers. The incidence of toxicity in the first three cycles was compared between DPYD variant allele carriers and non-variant carriers. Subsequent to an initial implementation phase, this test was made available province-wide.Results: In nine months, 186 patients were tested and 14 were found to be heterozygous variant carriers. Fluoropyrimidine-related toxicity was higher in DPYD variant carriers. Of 127 nonvariant carriers who have completed chemotherapy, 18 (14%) experienced severe (grade ≥3, Common Terminology Criteria for Adverse Events version 5.0). Of note, 22% (3 patients) of the variant carriers experienced severe toxicity even after DPYD-guided dose reductions. For one of these carriers who experienced severe thrombocytopenia within the first week, DPYD testing likely prevented lethal toxicity. In DPYD variant carriers who tolerate reduced doses, a later 25% increase led to chemotherapy discontinuation. As a result, a recommendation was made to clinicians based on available literature and expert opinion specifying that variant carriers who tolerated two cycles without toxicity can have a dose escalation of only 10%.Conclusions: DPYD-guided dose reductions were a feasible and acceptable method of preventing severe toxicity in DPYD variant carriers. Even with dose reductions, there were variant carriers who still experienced severe fluoropyrimidine toxicity, highlighting the importance of adhering to guideline-recommended dose reductions. Following the completion of the pilot phase of this study, DPYD genotyping was made available province-wide in British Columbia.